Characteristics of the Biochemical Composition and Bioavailability of Phytoplankton-Derived Particulate Organic Matter in the Chukchi Sea, Arctic - Bo Kim; Jinyoung Jung; Youngju Lee; Kyoung-Ho Cho; Jong-Ku Gal; Sung-Ho Kang; Sun-Yong Ha (Water, 2020)
Analysis of the biochemical composition (carbohydrates, CHO; proteins, PRT; lipids, LIP) of particulate organic matter (POM, mainly phytoplankton) is used to assess trophic states, and the quantity of food material is generally assessed to determine bioavailability; however, bioavailability is reduced or changed by enzymatic hydrolysis. Here, we investigated the current trophic state and bioavailability of phytoplankton in the Chukchi Sea (including the Chukchi Borderland) during the summer of 2017. Based on a cluster analysis, our 12 stations were divided into three groups: the southern, middle, and northern parts of the Chukchi Sea. A principal component analysis (PCA) revealed that relatively nutrient-rich and high-temperature waters in the southern part of the Chukchi Sea enhanced the microphytoplankton biomass, while picophytoplankton were linked to a high contribution of meltwater derived from sea ice melting in the northern part of the sea. The total PRT accounted for 41.8% (±7.5%) of the POM in the southern part of the sea, and this contribution was higher than those in the middle (26.5 ± 7.5%) and northern (26.5 ± 10.6%) parts, whereas the CHO accounted for more than half of the total POM in the northern parts. As determined by enzymatic hydrolysis, LIP were more rapidly mineralized in the southern part of the Chukchi Sea, whereas CHO were largely used as source of energy for higher trophic levels in the northern part of the Chukchi Sea. Specifically, the bioavailable fraction of POM in the northern part of the Chukchi Sea was higher than it was in the other parts. The findings indicate that increasing meltwater and a low nutrient supply lead to smaller cell sizes of phytoplankton and their taxa (flagellate and green algae) with more CHO and a negative effect on the total concentration of POM. However, in terms of bioavailability (food utilization), which determines the rate at which digested food is used by consumers, potentially available food could have positive effects on ecosystem functioning.